1991
DOI: 10.1007/bf01973712
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of chelating agents against renal toxicity of gold sodium thiomalate in rats

Abstract: The protective effects of various chelating agents such as D-penicillamine (D-PEN), 2,3-dimercaptosuccinic acid (DMSA), 2,3-dimercaptopropane sulphonate (DMPS), and N-(2-mercapto-2-methylpropanoyl)-L-cysteine (bucillamine), on the renal damage induced by gold sodium thiomalate (AuTM) in rats were studied. Rats were injected i.v. with AuTM at doses of 0.026, 0.066, 0.132, and 0.198 mmol/kg. Urinary excretion of protein, aspartate aminotransferase (AST), and glucose in rats injected with AuTM significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Experimental animal studies have demonstrated that DMSA and DMPS are efficient antidotes against acute gold intoxication and efficiently reduce the toxicity of ip-administered sodium bis(thiosulfato)gold(I) 194 or the nephrotoxicity of injected sodium thiomalate . In these and other studies, MSA, DMPS, and DPA significantly enhanced the excretion of gold after injection of gold compounds to rats or mice.…”
Section: Goldmentioning
confidence: 79%
See 1 more Smart Citation
“…Experimental animal studies have demonstrated that DMSA and DMPS are efficient antidotes against acute gold intoxication and efficiently reduce the toxicity of ip-administered sodium bis(thiosulfato)gold(I) 194 or the nephrotoxicity of injected sodium thiomalate . In these and other studies, MSA, DMPS, and DPA significantly enhanced the excretion of gold after injection of gold compounds to rats or mice.…”
Section: Goldmentioning
confidence: 79%
“…195 In these and other studies, [196][197][198][199] MSA, DMPS, and DPA significantly enhanced the excretion of gold after injection of gold compounds to rats or mice.…”
Section: Goldmentioning
confidence: 97%
“…It has also been successfully used for elemental, inorganic and organic mercury, arsenic, antimony, and copper chelation in humans [136,138,[149][150][151][152]. In animal experiments, meso-DMSA was an efficient chelator for gold [153][154][155][156] and nickel [104,105]. Controversial results were obtained for cadmium [73,75,157,158], thallium [136,159], and platinum, either for tissue platinum reduction, or for platinum nephrotoxicity [160][161][162][163].…”
Section: Meso-23-dimercaptosuccinic Acid (Succimer Meso-dmsa)mentioning
confidence: 98%